Roadmap to emergency remote teaching. Issue 199 (30th June 2022) - Daneshmand, Angela; Harris, Michelle; Viviani, Donn A.
Abstract: This chapter captures the authors' voices as faculty who were abruptly required to learn how to teach courses remotely in response to the COVID‐19 pandemic. They share how they successfully made changes and stayed committed to maintaining high standards in an online environment. Based on these experiences, they present recommendations for adaptations of active learning techniques from face‐to‐face (F2F) courses to online equivalents. Their roadmap to success focuses on key factors that contributed to increased student success and retention including: flexibility, a commitment to active learning methodologies, and fostering strong classroom communities.